Visual Research of Rossi Cigarette Packaging by Bahasa Rupa Primadi Tabrani Methode - A B Hardoyo (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
The purpose of this research is to conduct an analysis of the Rossi brand cigarette packaging design. Cigarette packaging is interesting to study, because in Indonesia there are very many cigarettes circulating in the market, either with international brands or local brands, with large-scale or small-scale industries or home industries. The method used in this study is to measure using the theory of Primadi Tabrani Bahasa Rupa, with a research discussion carried out in the form of photo, typography, colour, and layout on Rossi brand cigarette packaging. Primadi Tabrani’s theory of visual language is divided into two, namely NPM, namely Naturalist-Perspective-Momenopname and RWD, namely Space-Time-Flat. In this research on Rossi’s cigarette packaging, the visual language used is Naturalist-Perspective-Momenopname. The results obtained from this research aim to get a conclusion about the visual impression on the packaging. From this research, it can be concluded that red is used to attract attention because it has the longest wavelength compared to other colors. Impressions are quickly displayed from a bold front photo and a thinner or transparent back photo. From the typographical element, the masculine impression does not look like on cigarette packaging in general, but a bold impression that can be seen. Meanwhile, from the layout side, the aggressive impression is visible.